Judicial Review of Constitutional Amendments: Comparison Between India, Germany, Colombia, and the Relevancy with Indonesia - Novendri Nggilu; Mohamad Rivaldi Moha; Muhammad Ridho Sinaga; Adelia Rachmaniar (Lex Scientia Law Review, 2024)
The purpose of this study is to explore the urgency for a judicial review of the constitutionality of Indonesia's constitutional amendments. In addition, it explores, using Germany, Colombia, and India as comparative materials, the practice of judicial review regarding the constitutionality of constitutional amendments. The main writing approach used in this article, which examined the constitutional texts of Germany, Indonesia, Colombia, India, and Germany, was a comparative one. Similar provisions that are unchangeable explicitly or implicitly may be found in the constitutions of Colombia, Germany, India, and Indonesia. However, there are fundamental differences in efforts to protect, maintain and preserve these unchangeable provisions (as the fundamental structure and identity of the Constitution) in reviewing the constitutionality of constitutional amendments. This mechanism is practiced in India, Germany and Colombia but not in Indonesia. However, if studied carefully, 3 aspects show the urgency of implementing this mechanism in Indonesia: 1) historical aspects (the existence of past events regarding constitutional changes or transitions that are normatively unconstitutional; 2) philosophical and juridical aspects (the existence of Pancasila as state ideology as well as constitutional identity and the existence of Article 37 paragraph (5) which clearly states that the Form of the Republic of Indonesia cannot be changed); and 3) sociological aspects (the issue of constitutional amendments which seems to be patterned at the end of each president's term of office to extend the period of the president's term of office to three terms). These three aspects are the primary consideration and basis for implementing a mechanism for reviewing the constitutionality of constitutional amendments so that the fundamental structure and identity of the Indonesian Constitution are not damaged or eliminated by parliament through constitutional amendment activities.